European Diplomat-researchers’ (18th-19th cc.) Contribution to Caucasian Studies - Chantladze, Iza; Odzeli, Marika (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2022)
The article discusses the contributions of European scholars to the study of Kartvelian (Georgian) languages. The focus is on Oliver Wardrop's English-Svanetian Vocabulary, which, despite its errors, provides valuable infor- mation about the Svan language. The article also mentions the importance of European Diplomat-researchers’ (George Ellis, Johann Güldenstädt, Demetrius Peacock, Peter Pallas) efforts and D. Peacock’s Georgian-Mingrelian-Laz-Svan- Abkhaz vocabulary.